Modelling the deflection of rowing oar shafts - Laschowski, B.; Hopkins, C. C.; de Bruyn, J. R.; Nolte, V. (Sports Biomechanics, 2017)
The deflection of rowing oar shafts subjected to a static load was investigated. Two sets of sculling oars of different design stiffness were tested at three different lengths from 2.66 to 2.70m. Loads up to 201N were applied to the blade end of the oar shafts, and deflections were measured at six positions along the length of the shafts. The experimental results were compared with theoretical predictions obtained by modelling the oar shafts as homogenous end-loaded cantilever beams. The results show that the oar shafts are not uniform, in contradiction to the assumed model, but rather are most compliant near the sleeves and up to 80% stiffer towards the blades. The effect of oar shaft stiffness and length on the deflection angle at the blade end of the oar shaft was at most 1.18±0.01°. The measured variation of stiffness along the shaft has implications for boat propulsion and rowing performance. ABSTRACT FROM AUTHOR